COMMUNITY EMPOWERMENT THROUGH ERGONOMICS TRAINING WITH LOCAL WISDOM ORIENTED TO IMPROVE QUALITY OF SCULPTOR HEALTH IN THE PELIATAN VILLAGE, UBUD, GIANYAR, BALI-INDONESIA - Sutajaya, I Made (BALI MEDICAL JOURNAL, 2014)
Background: Until recently, data applied for reference of Balinese workers in their work stations and processes, including anthropometric data still applying secondary data source from literature review. This was probably inappropriate due to different size, since the literature data generally on the basis of western size of anthropometry. The objective of this research, therefore, was to establish community empowerment through ergonomics training with local wisdom oriented to improve the sculptor health care quality and productivity. Ergonomics training through workshops conducted with a systemic, holistic, interdisciplinary, and participatory (SHIP) approach. The training is done to make people aware of the work as a sculptor that is very important to apply ergonomics in the workplace. The results showed that ( a) participants judge that ergonomics workshop can open their insights about the importance of the application of ergonomics in the workplace, (b) work equipment is not in accordance with sculptor anthropometric, (c) inadequate working conditions, because the workers were exposed to noise working tool more than 80 decibel and the room temperature exceeds 34OC and work a lot of cockroaches and rats roam, and (d) the data of sculptor health quality is very poor, increase the workload at about13.5 %, musculoskeletal complaints at about 41.3 % , and fatigue at about 46.8 % ( p < 0.05 ) between before and after working. That means the work is very necessary sculptor redesigned in order to achieve comfort, safe, healthy, effective, and efficient of working conditions. It can be concluded that the ergonomics training with local wisdom oriented is required in an effort to implement the principles of ergonomics to achieve adequate health care quality sculptors and maximum productivity.